Representing Global Soil Erosion and Sediment Flux in Earth System Models. (3rd January 2022) - Tan, Zeli; Leung, L. Ruby; Li, Hong‐Yi; Cohen, Sagy
Abstract: Soil erosion produces enormous amounts of sediment, carbon, and nutrient fluxes from land to rivers, thus playing crucial roles in global biogeochemical cycles and food security. To predict soil erosion in the context of climate and land use changes, we explicitly parameterize cropland management actions (i.e., irrigation, conserved agriculture, and crop residue management) and geological factors (i.e., lithology and glacier) in the Energy Exascale Earth System Model (E3SM) soil erosion module. The erosion model is calibrated using a global‐scale regionalized parameter calibration method. The spatial variabilities of the modeled and the Revised Universal Soil Loss Equation (RUSLE) based benchmark soil erosion are consistent across vegetation, climate and soil properties. Compared with independent data, our model shows a bias reduction in 59% of the observations relative to the RUSLE‐based soil erosion, with 53% of the bias reduction exceeding 50%. This improvement is mainly due to a better representation of the topographic effect on soil erosion. Our results indicate that conserved agriculture practices have effectively reduced soil erosion in cropland by over 25% in the United States and Argentina. In contrast, irrigation has increased soil erosion in many Asian countries. For upland sediment flux, our model is consistent with the WBMsed benchmark data in inter‐basin variability but could be more skillful in simulating intra‐basin variability because it couples soil erosion and sediment flux explicitly. The developed model provides useful skills for more realistic predictions of soil erosion and river sediment dynamics under environmental changes. Plain Language Summary: Soil erosion plays a crucial role in global biogeochemical cycles and food security but is rarely represented in climate models. To predict soil erosion in the context of climate and land use changes, we represent the effects of cropland management practices on soil erosion in the Energy Exascale Earth System Model (E3SM) soil erosion module. Our model demonstrates good performance in simulating the spatial variability of global soil erosion and upland sediment flux. Particularly, our simulations show that conserved agriculture practices have effectively reduced soil erosion in cropland by over a quarter in the United States and Argentina. In contrast, irrigation has increased soil erosion in cropland greatly in many Asian countries, such as India and China. Our simulations also show that deforestation will increase sediment flux in tropical rainforest watersheds rapidly. The developed model provides useful skills for more realistic predictions of soil erosion and river sediment dynamics in response to environmental changes. Key Points: The new ELM‐Erosion model that represents cropland management and geological factors reproduce global soil erosion and sediment flux Our simulation shows that conservation agriculture has greatly reduced soil erosion in well‐adopted countries, such as USA and Argentina Our result indicates that deforestation will increase sediment flux rapidly in tropical river basins of large rainforest coverage